The Design of Medical Record Retention Implementation Guidelines at RSUD Balaraja Kabupaten Tangerang - Fatimah, Dwiyani Nur; Dewi, Deasy Rosmala (Akademi Perekam dan Informasi Kesehatan Imelda, 2026)
RSUD Balaraja Kab. Tangerang already has an SPO for the retention of active medical record files into inactive medical records and an SPO for the destruction of medical record files, there is no archive retention schedule yet. For the implementation of the reduction of medical records according to schedule, a procedure guideline is made. This study aims to design a procedure guideline for the reduction of medical records using the Delphi method which was carried out in October 2024 - November 2024. Data collection through observation of the medical record room, interviews with the head of the medical record installation and a questionnaire for the application of the Delphi method, with 5 stakeholders consisting of the Head of Medical Services, the Medical Service Operational Work Team, the Public Relations and Program Planning Administration Work Team, the Treasurer, and the Head of the Medical Record Installation. The results of this study describe the facilities and infrastructure and procedures for implementing the reduction of medical records at RSUD Balaraja Kab. Tangerang, preparing a guideline for the management of medical record reduction, verifying the results of filling out the questionnaire that has been agreed upon by stakeholders with a standard deviation of 0 which means there is no difference of opinion and proposing the design of a guideline for the management of medical record reduction consisting of chapter 1 definition, chapter 2 scope, chapter 3 procedures, and chapter 4 documentation. The conclusion is a draft design of a guideline for the management of medical record reduction which contains the procedures and schedule for the implementation of medical record reduction at RSUD Balaraja Kab. Tangerang.